2021
DOI: 10.3390/molecules27010058
|View full text |Cite
|
Sign up to set email alerts
|

How the Chemical Properties of GBCAs Influence Their Safety Profiles In Vivo

Abstract: The extracellular class of gadolinium-based contrast agents (GBCAs) is an essential tool for clinical diagnosis and disease management. In order to better understand the issues associated with GBCA administration and gadolinium retention and deposition in the human brain, the chemical properties of GBCAs such as relative thermodynamic and kinetic stabilities and their likelihood of forming gadolinium deposits in vivo will be reviewed. The chemical form of gadolinium causing the hyperintensity is an open questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 149 publications
0
16
0
Order By: Relevance
“…The kinetic inertness combined with the thermodynamic stability is a good predictor for in vivo complex stability. 33 The ion exchange ICP-MS analytical investigation of the Gd complexes before and after 3 weeks incubation with human serum reflects both the kinetic inertness and the thermodynamic stability under physiological conditions. Gadoquatrane showed no release of Gd 3+ within 3 weeks at 37°C in pooled human serum, and the complex stability of gadoquatrane was in the same range to other macrocyclic ( q = 1) GBCAs.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic inertness combined with the thermodynamic stability is a good predictor for in vivo complex stability. 33 The ion exchange ICP-MS analytical investigation of the Gd complexes before and after 3 weeks incubation with human serum reflects both the kinetic inertness and the thermodynamic stability under physiological conditions. Gadoquatrane showed no release of Gd 3+ within 3 weeks at 37°C in pooled human serum, and the complex stability of gadoquatrane was in the same range to other macrocyclic ( q = 1) GBCAs.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic application of GBCAs is currently considered largely safe in patients with normal renal function. However, after repeated administration of mainly linear GBCAs, retention of gadolinium (Gd) within different organs was reported to occur in patients without renal impairment 2,3 . This resulted in restrictions on the use of linear GBCAs by the European Medicines Agency (EMA/625317/2017) 4 and class warnings by the US Food and Drug Administration 5…”
mentioning
confidence: 99%
“…However, after repeated administration of mainly linear GBCAs, retention of gadolinium (Gd) within different organs was reported to occur in patients without renal impairment. 2,3 This resulted in restrictions on the use of linear GBCAs by the European Medicines Agency (EMA/625317/2017) 4 and class warnings by the US Food and Drug Administration. 5 Within central nervous system (CNS) structures, Kanda et al 6 revealed for the first time a positive correlation between previous administrations of linear GBCAs and T1 hyperintensities in unenhanced brain MRI scans, in particular in the dentate nucleus (DN).…”
mentioning
confidence: 99%
“…However, when using these systems, potential toxic effects of the gadolinium salts should be considered as well as effects of the strong magnetic field and its gradient that are described above. Gadolinium derivatives are widely used as contrast agents in magnetic resonance imaging (MRI) techniques so their toxicity has been extensively studied [61][62][63]. An ability of the Gd 3+ to compete with Ca 2+ in active centers of Ca 2+ -binding enzymes underlies gadolinium toxicity because Ca 2+ substitution with Gd 3+ can interrupt critically important Ca 2+ -dependent pathways [61].…”
Section: Maglev Systems Based On Permanent Magnetsmentioning
confidence: 99%
“…Gadolinium derivatives are widely used as contrast agents in magnetic resonance imaging (MRI) techniques so their toxicity has been extensively studied [61][62][63]. An ability of the Gd 3+ to compete with Ca 2+ in active centers of Ca 2+ -binding enzymes underlies gadolinium toxicity because Ca 2+ substitution with Gd 3+ can interrupt critically important Ca 2+ -dependent pathways [61]. To decrease toxicity, gadolinium-based substances, which are used in MRI, enclose Gd 3+ in the complex that is expected to remain chelated in the human body and be excreted intact.…”
Section: Maglev Systems Based On Permanent Magnetsmentioning
confidence: 99%